New at-sea records of pelagic seabirds in the South Atlantic Ocean and Antarctica - Orgeira, Tomás José Luis (2013)
In austral summer 1994-95, 2009, 2010, 2011 and 2012 during a ship-based seabird survey in the south Atlantic and Antarctica we documented at-sea distributions of Buller´s albatross (Thalassarche bulleri), Atlantic petrel (Pterodroma incerta), Softplumaged petrel (P. mollis), Kerguelen petrel (Lugensa brevirostris), and Great-winged petrel (P. macroptera). In some cases, sightings were considered as extralimital but for other species, their distributions need updating. Atlantic Petrel, for example, has been regularly observed in the Drake Passage and north of the Antarctic Peninsula for about 30 years, but the species distribution has not been updated in the literature. Our results will contribute to update the at sea species` distributions and their changes.